Restoration of Hydrogen Sulfide Production in Diabetic Mice Improves Reparative Function of Bone Marrow Cells. Issue 19 (8th November 2016) - Cheng, Zhongjian; Garikipati, Venkata Naga Srikanth; Nickoloff, Emily; Wang, Chunlin; Polhemus, David J.; Zhou, Jibin; Benedict, Cynthia; Khan, Mohsin; Verma, Suresh K.; Rabinowitz, Joseph E.; Lefer, David; Kishore, Raj
Abstract : Background: Bone marrow cell (BMC)–based treatment for critical limb ischemia in diabetic patients yielded a modest therapeutic effect resulting from cell dysfunction. Therefore, approaches that improve diabetic stem/progenitor cell functions may provide therapeutic benefits. Here, we tested the hypothesis that restoration of hydrogen sulfide (H2 S) production in diabetic BMCs improves their reparative capacities. Methods: Mouse BMCs were isolated by density-gradient centrifugation. Unilateral hind limb ischemia was conducted in 12- to 14-week-old db/+ and db/db mice by ligation of the left femoral artery. The H2 S level was measured by either gas chromatography or staining with florescent dye sulfidefluor 7 AM. Results: Both H2 S production and cystathionine γ-lyase (CSE), an H2 S enzyme, levels were significantly decreased in BMCs from diabetic db/db mice. Administration of H2 S donor diallyl trisulfide (DATS) or overexpression of CSE restored H2 S production and enhanced cell survival and migratory capacity in high glucose (HG)–treated BMCs. Immediately after hind limb ischemia surgery, the db/+ and db/db mice were administered DATS orally and/or given a local intramuscular injection of green fluorescent protein–labeled BMCs or red fluorescent protein–CSE–overexpressing BMCs (CSE-BMCs). Mice with hind limb ischemia were divided into 6 groups: db/+, db/db, db/db+BMCs, db/db+DATS, db/db+DATS+BMCs, and db/db+CSE-BMCs. DATS and CSE overexpression greatly enhanced diabetic BMC retention in ischemic hind limbs followed by improved blood perfusion, capillary/arteriole density, skeletal muscle architecture, and cell survival and decreased perivascular CD68 + cell infiltration in the ischemic hind limbs of diabetic mice. It is interesting to note that DATS or CSE overexpression rescued high glucose–impaired migration, tube formation, and survival of BMCs or mature human cardiac microvascular endothelial cells. Moreover, DATS restored nitric oxide production and decreased endothelial nitric oxide synthase phosphorylation at threonine 495 levels in human cardiac microvascular endothelial cells and improved BMC angiogenic activity under high glucose condition. Last, silencing CSE by siRNA significantly increased endothelial nitric oxide synthase phosphorylation at threonine 495 levels in human cardiac microvascular endothelial cells. Conclusions: Decreased CSE-mediated H2 S bioavailability is an underlying source of BMC dysfunction in diabetes mellitus. Our data indicate that H2 S and overexpression of CSE in diabetic BMCs may rescue their dysfunction and open novel avenues for cell-based therapeutics of critical limb ischemia in diabetic patients. Abstract : Supplemental Digital Content is available in the text.